Influencing of pollution on power properties of hydrocarbonaceous fuel - Матвєєва, О.Л.; Кравець, І.А. (Proceedings of National Aviation University (archive), 2004)
The result investigation of influencing of a dispersion pollution of hydrocarbonaceous fuel on its power condition are reviewed. The intensity of change of a surface of a contact of a disperse phase is determined at splitting mechanical pollution in fuel. Is shown, that the process of pollution negatively influences power properties of fuel.